The Level of Teaching Practices Supporting 21st-Century Skills Among Social Studies Teachers A Field Study in the Primary Stage (First Cycle) in Latakia City (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The aim of the research is to identify the level of teaching practices that support 21st century skills among social studies teachers (critical thinking, cooperation and participation, communication, creativity and innovation, self-direction, global connections, local connections, use of technology) in the primary education stage (first cycle) in the city of Lattakia. And to study whether there are statistically significant differences between their average scores according to the variables (gender, number of years of experience, academic qualification). The research adopted the descriptive approach, and the research community included all teachers of the first cycle of primary education in the city of Lattakia, numbering (2225) male and female teachers distributed over (23) schools according to the official statistics of the Directorate of Education in the city of Lattakia. A simple random sample was drawn at a rate of (15%) from the original community, so that the number of its members reached (334) male and female teachers. The researcher distributed the questionnaire, the research tool, to them, represented by (a questionnaire) designed by the researcher, and (318) complete questionnaires were retrieved and valid for statistical analysis. The results showed that the level of teaching practices supporting 21st century skills in general among the research sample members was at an average level, and there was no statistically significant difference between their average scores in the level of teaching practices according to the gender variable, while there were statistically significant differences according to the years of experience variable in favor of less experience, and according to the academic qualification variable in favor of higher qualification.